Identity construction in the comments section of TomandLorenzo.com - Prantl, Aline (2016)
Virtual spaces as sites of social interactions and therefore identity work have become common over the past few decades. Alongside, research focus on such spaces has increased. This MA thesis constitutes a small contribution to the study of interactional identity building through computer mediated communication. The study was conducted on data gathered from a subsection of popular-culture blog tomandlorenzo. The aim was to identify how interactants in this space interactively work their identities. The qualitative discourse analysis focused on three mechanics of identity building, those of indexicality, performativity and stance taking. The investigation also took the influence of the medium on interactional identity work into account.Findings were that participants used indexicality mostly to position themselves in a broader social context independent of the local community. Contrarily, performances of identity in the Goffmanian sense were used to authenticate contributors in this specific virtual space. Displays of sympathy and emphases on similarities simultaneously served to convey individual’s identities and build local group belonging. Interactants’ stances and stance uptakes further assisted in positioning individuals inside the group and augmented a sense of community. The emphasis on community building was also apparent from the lack of dissent and conflicts in the data. The study reinforced previous research findings that identity is an accumulation of overlapping and complementary facets that are influenced by the medium of interaction.